2017
DOI: 10.18632/oncotarget.22127
|View full text |Cite
|
Sign up to set email alerts
|

Calcium homeostasis and endoplasmic reticulum stress are involved in Salvianolic acid B-offered protection against cardiac toxicity of arsenic trioxide

Abstract: Arsenic trioxide (ATO) is a potent anticancer agent used to treat acute promyelocytic leukemia. However, its cardiotoxicity limits ATO’s widespread clinical use. Previous studies demonstrated that ATO may aggravate Ca2+ overload and promote endoplasmic reticulum stress (ERS). Salvianolic acid B (Sal B) is cardioprotective against ATO and enhances ATO’s anticancer activities. The present study assessed whether the Sal B protective effect was related to maintenance of Ca2+ homeostasis and inhibition of ER stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…ATO is a potent treatment for APL; however, due to the cardiotoxicity of ATO, many patients with cancer are unable to receive more efficient treatment [18]. Previous research by our team has shown that salvianolic acid B (Sal B) had a protective effect against cardiotoxicity induced by ATO [19]. Subsequently we found that Sal A also suppresses ATO-induced cardiac dysfunction in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…ATO is a potent treatment for APL; however, due to the cardiotoxicity of ATO, many patients with cancer are unable to receive more efficient treatment [18]. Previous research by our team has shown that salvianolic acid B (Sal B) had a protective effect against cardiotoxicity induced by ATO [19]. Subsequently we found that Sal A also suppresses ATO-induced cardiac dysfunction in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…Oxidative stress is widely considered as one of the main mechanisms underlying the toxicity of ATO [19]. We previously showed that Sal A decreased oxidative stress and intracellular ROS levels, and increased antioxidant enzyme activity against ATO in vitro [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study further examined the anti-atherosclerotic effects of Sal B and investigated the underlying mechanisms. Previous studies have confirmed that Sal B has anti-oxidative effects and eliminates superoxide anion radicals (O 2− ), thereby suppressing hydrogen peroxide (H 2 O 2 )-induced apoptosis (10,11). Another study indicated that Sal B promotes human umbilical vein endothelial cell (HUVEC) proliferation (12).…”
Section: Introductionmentioning
confidence: 97%
“…ER stress itself is intimately linked to intracellular Ca 2+ handling [8,9,10,11,12,13,14]. Treatment of cells with thapsigargin (TG) or cyclopiazonic acid, inhibitors of the sarco/endoplasmic Ca 2+ ATPase (SERCA), leads to ER Ca 2+ depletion and ER stress [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%